Changes in the Dynamics of Indonesian Tourists Regarding the Information Adoption Process in the Digital Era - Aqlia Pratiwi; Bambang Dwi Prasetyo; Ananda Sabil Hussein (Universitas Negeri Gorontalo, 2025)
In the age of abundant information, tourists increasingly turn to digital reviews to make quick informed decisions about destinations, but how these reviews shape their choices remains an important but underexplored topic. This study investigates the influence of the peripheral route from the Elaboration Likelihood Model (ELM), focusing on the dimensions of Information Quantity and Product Ranking, on information adoption by tourists for the Milenial Glow Garden. The findings demonstrate that a high volume of reviews and favorable product ratings act as significant peripheral cues, guiding tourists' decision-making processes, particularly when they lack the motivation or ability to engage in deep cognitive processing. Aligning with ELM, it is evident that in the digital realm, tourists often rely on social proof—specifically review quantity and ratings—as a faster, more convenient means of decision-making. The study further reveals that younger tourists (aged 18 to 35) are especially influenced by review quantity and ratings, opting for decisions based on aggregated information. These cues enhance tourists’ perceptions of a destination’s credibility and appeal, especially for those motivated by FOMO (Fear of Missing Out) and seeking modern, high-tech experiences. The results underline the growing reliance on digital information in the decision-making process, with review volume and star ratings significantly shaping urban tourists' perceptions and choices. This research provides valuable insights for digital tourism marketing, offering strategies for destination managers like Milenial Glow Garden to attract tourists who rely on heuristics, creating tech-driven and engaging tourism experiences.